2011
DOI: 10.1017/s0017089511000085
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Stabilisation of a Tree-Shaped Network of Strings With Variable Coefficients

Abstract: Abstract. In this paper, we deal with a tree-shaped network of strings with a fixed root node. By imposing velocity feedback controllers on all vertices except the root node, we show that the spectrum of the system operator consists of all isolated eigenvalues of finite multiplicity and is distributed in a strip parallel to the imaginary axis under certain conditions. Moreover, we prove that there exists a sequence of eigenvectors and generalised eigenvectors that forms a Riesz basis with parentheses, and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In [1], the authors apply transparent boundary conditions at all simple nodes in addition to velocity feedback controls at the multiple nodes, in order to obtain finite time stabilization. For the exponential stabilization of star-shaped networks using spectral methods, we refer to [13] where the controls are applied at the multiple nodes and all simple nodes but one, and [41] where the controls are applied at all simple nodes but one. In [12], the authors showed that, for star-shaped networks, finite time stability is achieved by applying velocity feedback controls at all simple nodes, and that exponential stability is still achieved if one of the controls is removed from time to time.…”
Section: 3mentioning
confidence: 99%
“…In [1], the authors apply transparent boundary conditions at all simple nodes in addition to velocity feedback controls at the multiple nodes, in order to obtain finite time stabilization. For the exponential stabilization of star-shaped networks using spectral methods, we refer to [13] where the controls are applied at the multiple nodes and all simple nodes but one, and [41] where the controls are applied at all simple nodes but one. In [12], the authors showed that, for star-shaped networks, finite time stability is achieved by applying velocity feedback controls at all simple nodes, and that exponential stability is still achieved if one of the controls is removed from time to time.…”
Section: 3mentioning
confidence: 99%
“…The energy is in some sense this considered norm. The stabilization of the system (1) and some more complicated configurations has been considered in a lot of papers [1,3,5,22,15],. .…”
Section: N J=1mentioning
confidence: 99%
“…Let (f, g) ∈ D(A) and 0 ≤ j ≤ N. For the first claim, we use integration per parts in (21) and (22) and hence we get λφ 0 (x) = λK 1 (x, λ)f 0 (0) + K f,g 2 (x, λ)…”
Section: This Writes As a Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Under certain conditions, they proved that the networks system is exponentially stable, but have no estimate of the decay rate. More recent results on stabilization and supper-stability of the 1-d wave networks, we refer to [53,54,52], [19,18]. About research development for the general 1-d wave network, we refer to literatures [51] and [49].…”
mentioning
confidence: 99%